Mode II interlaminar fracture testing on different type of resins and fiber forms - Wong, Guan Yuan, 1986-; Yob Saed Ismail, supervisor; Fakulti Kejuruteraan Mekanikal (2009)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2009